A study of visual representation in the selected Malays films in the year of 90’s / Siti Jamilah Md Nor - Md Nor, Siti Jamilah (2016)
Film is one of the communication tools that have the power to reach out to the society and also a medium for expression with a creative combination of photography and audio technology. Thus, it is important for us to know the meaning behind the visuals especially from the Malay movies produced in the 90’s to ensure that the people can understand the messages that are being conveyed. This objective of this research is to analyze the understanding, application and achievement of visual representation in selected Malay films in the era of 90’s among film directors. This research is to provide guidance to the producer, the director, art director, film students, movie audience and society. A qualitative method was employed the used of interview and observation to emphasizes on objectives measurements. The interview were analysed via voice and visual recording methods while film observations were analyzed by using the semiotic theory (icon, index and symbol) of Alexander Charles Pierce. The findings indicated that level of understanding among filmmakers varies and this is likely as they have different educational backgrounds. However it is not entirely dependent on their own but it also involves all members of the production. Meanwhile, director aware film is a fundamental feature of daily life which shows our own culture. Overall, research revealed that the level of visual representation in 90’s is still modest because it identified only applied depending on the requirements of the genre only.